The National Strategic Plan and the problem of university education - Gutiérrez Huby, Manuel Guillermo (2018)
This article arises in view of the objective need to determine what are the causes why the Peruvian university, in general, is facing the current crisis that can be perceived as a product of the lack of application of a good part of the scope established in the National Strategic Plan regarding the university and its operation. This lack of application is what has resulted in the conditions that are seen within the problematic of university education, trying to explain it in the best way to understand this conflictive situation. The general conclusion is aimed at determining guidelines that lead to understand the underlying problem and to be aware of the need for competent authorities to act on the aforementioned crisis in order to seek to reverse the current situation that is occurring.